PENGARUH KEPEMIMPINAN, KOMUNIKASI ORGANISASI DAN KOMPETENSI APARATUR TERHADAP KINERJA PUSKESMAS DI KOTA PEKANBARU DENGAN INOVASI SEBAGAI VARIABEL MODERASI - Lidya Yasmin Nasution; Zulfadil Zulfadil; Syapsan Syapsan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Health development is essentially an effort carried out by all Indonesians aimed at increasing awareness of the components, willingness, and ability to live healthy for everyone in order to realize the highest degree of public health, as an investment for the development of socially and economically productive human resources. economical. The Puskesmas itself is a Technical Implementation Unit of the Regency/City Health Office, each of which its performance will build the performance of the Regency/City Health Office. For puskesmas performance, the City/Regency Health Office uses the Puskesmas Performance Assessment (PKP) instrument. The PKP instrument is prepared by the Provincial Health Office so that the uniform is used for one province. Through surveys and interviews conducted by researchers in several health centers, based on the perceptions of respondents, researchers found several problems including the leadership of several puskesmas heads which were considered not good enough to provide the necessary direction and policies to improve the performance of puskesmas, internal and external health centers that were it is still considered good enough and the human resources owned by the puskesmas are still sufficient which is indicated by the assignments that are not in accordance with the abilities and expertise possessed by the officers and the lack of innovation made by the puskesmas in providing services to the community. This study aims to determine the effect of leadership, organizational communication on the performance and competence of the apparatus. To analyze service innovation as a moderating variable between leadership, organizational communication and apparatus competence with the performance of Puskesmas in Pekanbaru City. In this study, the sample was 101 people. The data used in this study are primary data and secondary data and the data collection method is a questionnaire. The data analysis technique used in this research is Moderate Regression Analysis. The results show that leadership has an effect on work innovation. Organizational communication has an effect on work innovation. Competence affects the organizational performance of employees. Leadership has a significant effect on employee organizational performance moderated by innovation. Organizational communication has a significant effect on organizational performance moderated by innovation. Competence has a significant effect on organizational performance moderated by innovation.